Assessment of the Effectiveness of Ectomycorrhizal Inocula to Promote Growth and Root Ectomycorrhizal Colonization in Pinus patula Seedlings Using the Most Probable Number Technique - Manuel Restrepo-Llano; Nelson W. Osorio; Juan D. León (Applied and Environmental Soil Science)
The aim of this study was to evaluate the response of Pinus patula seedlings to two inocula types: soil from a Pinus plantation (ES) and an in vitro produced inoculum (EM). The most probable number method (MPN) was used to quantify ectomycorrhizal propagule density (EPD) in both inocula in a 7-order dilution series ranging from 100 (undiluted inoculum) to 10−6 (the most diluted inoculum). The MPN method allowed establishing differences in the number of infective ectomycorrhizal propagules’ density (EPD) (ES=34 per g; EM=156 per g). The results suggest that the EPD of an inoculum may be a key factor that influences the successfulness of the inoculation. The low EPD of the ES inoculum suggests that soil extracted from forest plantations had very low effectiveness for promoting root colonization and plant growth. In contrast, the high EPD found in the formulated inoculum (EM) reinforced the idea that it is better to use proven high quality inocula for forest nurseries than using soil from a forestry plantation.